Co‐exposure to sunlight enhances the toxicity of naturally weathered Deepwater Horizon oil to early lifestage red drum (Sciaenops ocellatus) and speckled seatrout (Cynoscion nebulosus). (21st November 2016) - Alloy, Matthew; Garner, Thomas Ross; Bridges, Kristin; Mansfield, Charles; Carney, Michael; Forth, Heather; Krasnec, Michelle; Lay, Claire; Takeshita, Ryan; Morris, Jeffrey; Bonnot, Shane; Oris, James; et al.
Abstract: The 2010 Deepwater Horizon oil spill resulted in the accidental release of millions of barrels of crude oil into the Gulf of Mexico. Photo‐induced toxicity following co‐exposure to ultraviolet (UV) radiation is 1 mechanism by which polycyclic aromatic hydrocarbons (PAHs) from oil spills may exert toxicity. Red drum and speckled seatrout are both important fishery resources in the Gulf of Mexico. They spawn near‐shore and produce positively buoyant embryos that hatch into larvae in approximately 24 h. The goal of the present study was to determine whether exposure to UV as natural sunlight enhances the toxicity of crude oil to early lifestage red drum and speckled seatrout. Larval fish were exposed to several dilutions of high‐energy water‐accommodated fractions (HEWAFs) from 2 different oils collected in the field under chain of custody during the 2010 spill and 3 gradations of natural sunlight in a factorial design. Co‐exposure to natural sunlight and oil significantly reduced larval survival compared with exposure to oil alone. Although both species were sensitive at PAH concentrations reported during the Deepwater Horizon spill, speckled seatrout demonstrated a greater sensitivity to photo‐induced toxicity than red drum. These data demonstrate that even advanced weathering of slicks does not ameliorate the potential for photo‐induced toxicity of oil to these species. Environ Toxicol Chem 2017;36:780–785. © 2016 SETAC